T329S Mutation in the FMO3 Gene Alleviates Lipid Metabolic Diseases in Chickens in the Late Laying Period - Jianlou Song; Mingyi Huang; Xuefeng Shi; Xianyu Li; Xia Chen; Zhaoxiang He; Junying Li; Guiyun Xu; Jiangxia Zheng (Animals, 2021)
The T329S mutation in flavin-containing monooxygenase 3 (FMO3) impairs the trimethylamine (TMA) metabolism in laying hens. The TMA metabolic pathway is closely linked to lipid metabolic diseases, such as atherosclerosis and fatty liver disease. We aimed to evaluate the effects of the T329S mutation in FMO3 on lipid metabolism in chickens during the late laying period. We selected 18 FMO3 genotyped individuals (consisting of six AA, six AT, and six TT hens) with similar body weight and production performance. The lipid metabolism and deposition characteristics of the laying hens with different genotypes were compared. The T329S mutation moderated the serum-lipid parameters in TT hens compared to those in AA and AT hens from 49 to 62 weeks. Furthermore, it reduced the serum trimethylamine N-oxide concentrations and increased the serum total bile acid (p < 0.05) and related lipid transporter levels in TT hens. Moreover, it significantly (p < 0.01) decreased atherosclerotic lesions and hepatic steatosis in TT hens compared to those in the AA and AT hens. Our findings may help improve the health status in laying hens during the late laying period.